1994
DOI: 10.1084/jem.179.4.1273
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 12 induces stable priming for interferon gamma (IFN-gamma) production during differentiation of human T helper (Th) cells and transient IFN-gamma production in established Th2 cell clones.

Abstract: SummaryInterleukin 12 facilitates the generation of a T helper type 1 (Thl) response, with high interferon 3' (IFN-3') production, while inhibiting the generation of IL-4-producing Th2 calls in polyclonal cultures of both human and murine T cells and in vivo in the mouse. In this study, we analyzed the effect of IL-12, present during cloning of human T cells, on the cytokine profile of the clones. The culture system used allows growth of clones from virtually every T cell, and thus excludes the possibility th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
220
0
3

Year Published

1998
1998
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(233 citation statements)
references
References 37 publications
10
220
0
3
Order By: Relevance
“…This would appear to be a mechanism for their stable commitment to the Th2 phenotype (37). In contrast, established human Th2 clones can still be induced by IL-12 to produce IFN-␥ (40). Our data indicate that in humans down-regulation of surface IFN-␥R2 is mainly involved in the prevention of IFN-␥-mediated apoptosis by T cells rather than an event intrinsically linked to the polarization of cells to the Th1 lineage (41).…”
Section: Effect Of Endogenous Ifn-␥ On Ifn-␥r2 Internalization In Tmentioning
confidence: 85%
“…This would appear to be a mechanism for their stable commitment to the Th2 phenotype (37). In contrast, established human Th2 clones can still be induced by IL-12 to produce IFN-␥ (40). Our data indicate that in humans down-regulation of surface IFN-␥R2 is mainly involved in the prevention of IFN-␥-mediated apoptosis by T cells rather than an event intrinsically linked to the polarization of cells to the Th1 lineage (41).…”
Section: Effect Of Endogenous Ifn-␥ On Ifn-␥r2 Internalization In Tmentioning
confidence: 85%
“…In addition, a further antitumour activity of IL-12 is its ability to induce IFN-g production by T cells, which in turn mediates antiangiogenic effects. [23][24][25] Previous studies have shown that the amount of IL-12 available at the tumour site is critical for tumour regression, since it determines the number and type of infiltrating leucocytes. 21 It may also mediate the antiangiogenic effect of IL-12, 18 although the relative contribution of these two effects to the antitumour activity of IL-12 is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…IL-12 induces the differentiation of T-helper1 (Th1) CD4+ cells, which are inducers of IFN-g production. 23 It has been reported that tumour treatment using IL-12 is associated with the expression of the cytokine IFN-g and chemokines such as IP-10 at the tumour site, inducing the antitumour effect through a direct toxic effect on the tumour cells or by activating potent antiangiogenic mechanisms. 24 The induced antiangiogenic mechanisms are complex and dependent both on the direct effect of the proinflammatory cytokines/chemokines on endothelial cells and the recruitment of effector NK and T-cells.…”
Section: Introductionmentioning
confidence: 99%
“…Por tanto, se ha estudiado la posibilidad de tratar la leishmaniasis con compuestos potenciadores de la respuesta inmune, proceso conocido El conocimiento del estado inmunológico de los pacientes con leishmaniasis puede ser una gran herramienta para lograr un tratamiento efectivo de las formas clínicas crónicas de difícil resolución con antimoniales pentavalentes. Por ejemplo, en algunos estudios con modelos experimentales en los que se utilizó IL-12, se ha observado que esta citocina tiene un papel importante en la iniciación o establecimiento de una respuesta T h l protectora con alta producción de lFNy que, a su vez, inhibe la generación de una respuesta Th2 (50,63). En los ratones susceptibles, la inmunoterapia con IL-12 durante las primeras semanas de infección previene el desarrollo de una respuesta tipo Th2 y promueve el desarrollo de una respuesta tipo Thl dependiente de lFNy que conlleva a la cura de las lesiones (49).…”
Section: Respuesta Al Tratamiento Y Producción De Citocinasunclassified